1989
DOI: 10.1002/anr.1780320420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salicylate on chondrocytes from osteoarthritic and contralateral knees of dogs with unilateral anterior cruciate ligament transection

Abstract: Salicylates suppress net glycosaminoglycan synthesis in articular cartilage. The inhibitory effect is greater in osteoarthritic (OA) cartilage than in normal cartilage. Whether the isolated OA chondrocyte is inherently more susceptible to the effects of salicylate on glycosaminoglycan metabolism has not been determined. The results of this study show that, after isolation from the extracellular matrix, normal and OA chondrocytes in suspension culture are similarly susceptible to the metabolic effects of salicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Although the rates of proteoglycan and collagen synthesis are increased, these events are accompanied by an increased rate of release of the newly synthesized proteoglycan from the cartilage matrix (6,35). Recently, this model has proved useful in determining effects of drugs on the development of the disease and the activity of the cartilage (36,37,39,62).Proteoglycans are a major component of the extracellular matrix of articular cartilage (20,33,45,49) and are vital in maintaining the function of the tissue. Proteoglycans of cartilage are complex glyco-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the rates of proteoglycan and collagen synthesis are increased, these events are accompanied by an increased rate of release of the newly synthesized proteoglycan from the cartilage matrix (6,35). Recently, this model has proved useful in determining effects of drugs on the development of the disease and the activity of the cartilage (36,37,39,62).Proteoglycans are a major component of the extracellular matrix of articular cartilage (20,33,45,49) and are vital in maintaining the function of the tissue. Proteoglycans of cartilage are complex glyco-…”
mentioning
confidence: 99%
“…Although the rates of proteoglycan and collagen synthesis are increased, these events are accompanied by an increased rate of release of the newly synthesized proteoglycan from the cartilage matrix (6,35). Recently, this model has proved useful in determining effects of drugs on the development of the disease and the activity of the cartilage (36,37,39,62).…”
mentioning
confidence: 99%
“…There is also evidence that some members of this group of drugs can have deleterious effects on bone and cartilage metabolism (13,32). Some drugs, such as salicylates and indomethacin may accelerate the destructive processes in osteoarthritic joints, depending upon the drug concentration (1,29,33). These detrimental outcomes have largely been derived from in vitro experimental studies of cartilage explant cultures and, while some drugs have demonstrated a negative effect, other members of this family of drugs have been shown to possibly improve, or protect, cartilage metabolism or not to have any effect at all (5, 17, 20, 30).…”
Section: Introductionmentioning
confidence: 99%
“…Injury to these structures can result in instability and "giving out" of the knee. In the dog an ACL tear usually results in rapidly progressive osteoarthritis of the knee joint [1,4,5,7,12,13,18,19,20,23], but this progression is not necessarily true in humans [2,6,8,14,15,21,22].…”
Section: Introductionmentioning
confidence: 99%